STUDY ON THE COEXISTENCE OF FRENCH REPUBLICAN VALUES AND MUSLIM CULTURE - Zhang, Huining (European journal for philosophy of religion, 2023)
France's "republican assimilation" immigration policy has been widely questioned, and the contradiction and estrangement between Muslim immigrants and the mainstream society seems to be deepening. This paper focuses on the coexistence of French republican values and Muslim culture, discusses and analyzes the French immigration policy and various social problems caused by Muslim immigrants in France, and puts forward suggestions on how to solve these problems. The study found that the high unemployment rate, the backward living environment, the discrimination brought by the society, and the dissatisfaction in the heart are the most important social survival pressure faced by the French Muslim immigrant groups under the background of the French republican assimilation policy and the era. From the perspective of French local people, the employment pressure, population pressure, welfare pressure and security pressure brought by Muslim immigrants have deepened their exclusion and resentment towards Muslim immigrants. In order to realize the harmonious coexistence of French republican values and Muslim culture, as the main body of French immigration issues, Muslims should not only integrate into the Republic with a positive attitude, but also overcome the inherent closeness of Islamic culture. Actively participate in the activities of French mainstream society through various channels, understand French culture in the activities, and improve the relationship with the mainstream French people. At the same time, France must build a "republic" immigration policy that keeps pace with the times. Find a migration integration model that can not only accommodate political and cultural diversity, but also solve social conflicts under the national system.